Improvement in quality of life in patients with Fistula-In-Ano, following surgical management, a prospective observational study - Chandrabose, Karpagavel; Nair, Velayudhan (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Background: Fistula-in-ano may lead to significant worsening of quality of life of affected person. But studies documenting the impact of treatment quality of life are very limited in Indian population. Hence the current study was conducted with an objective of assessing the improvement in quality of life in patients undergoing surgical management of fistuala-in-ano in a tertiary care teaching hospital in south India. Methodology: The current study was a prospective observational study, conducted in the department of general surgery of Dr. SMCSI Medical college hospital, between February and December 2016. A total of 45 subjects aged between 20 to 80 years, suffering from various types of fistual in ano, managed with surgical intervention were included in the study. Quality of life was before and after surgery was assessed by GIQLI questionnaire. Results: Among the 45 subjects, 71.11% were males majority were aged between 41 to 60 years. The proportion of Inter sphincteric fistula was 48.88% whereas Trans-sphincteric fistula and Supra sphincteric fistula were 33.33% and 17.77% respectively. Fistulectomy was conducted in 44.44% of cases. Fistulotomy and insertion of cutting setons were done in 31.11% and 24.44% cases. Mean values of symptoms pre and post-operative were 49.50 and 66.25 and the association was statistically significant (P=<0.01). Mean associated physical disease was 14.25 before surgery and the post-operative mean was 22.76 with a statistically significant mean difference (P=<0.01). Preoperative Mean values for emotions, social integration, and effects of treatment were 7.65, 8.26 and 3.00 respectively, whereas Post-operative means were 15.27, 14.40 and 3.65. There were statistically significant mean differences for Emotions, social integration and effects of treatment. Mean Total score of pre-surgery was 89.05 and post-surgery was 120.26 with a statistically significant mean difference. (P=<0.01). Conclusions: 1) There is a significant improvement in the quality of life postoperatively in patients of Fistula in ano. 2) GIQLI score is a useful tool to assess the quality of life in Fistula in ano patients.